Tác động của quản trị tri thức đến sự hài lòng và kết quả hoàn thành công việc của nhân viên ngân hàng - Trần Kim , Dung; Lê Thị Thanh , Tâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Research aims to examine the relationship between knowledge management, job satisfaction, and job performance for employees in banks. The research applies SEM and is based on a survey sample of 666 employees working within functional departments of banks in Ho Chi Minh city. The research results show the positive effects of knowledge management on job satisfaction and job performance. Job satisfaction plays a mediating role between knowledge management and job performance. The result also shows differences in these effects between domestic banks and banks with foreign direct investment. The results provide a basis for understanding the relationship among three concepts and key components of knowledge management in banks. This assists with the right strategies to improve bank performance.